Association of Physical Activity With Telomere Length Among Elderly Adults - The Oulu Cohort 1945 - Stenbäck, Ville; Mutt, Shivaprakash Jagalur; Leppäluoto, Juhani; Gagnon, Dominique D.; Mäkelä, Kari A.; Jokelainen, Jari; Keinänen-Kiukaanniemi, Sirkka; Herzig, Karl-Heinz (Frontiers in Physiology, 2019)
Introduction Physical activity (PA) has been shown to alleviate age-associated telomere shortening by reducing oxidative stress and inflammation. The effect of PA intensity and volume on telomere length is nonetheless unclear suggesting both protective and damaging effects. The aim of our study was to investigate the effects of exercise intensity and volume on telomere length in elderly adults from Northern Finland (65◦ latitude North). Methods 700 elderly subjects born in 1945 in the Oulu region were investigated. PA was measured during a 2-week period with a wrist-worn accelerometer. In addition, a questionnaire was used to assess sedentary time and to achieve longitudinal PA history and PA intensity. Relative telomere lengths (RTL) were determined from frozen whole blood using a qPCR-based method. Results RTLs were longer in women than men (0.031) and negatively correlated with age in both genders (men -0.210, p=0.000, women -0.174, p=0.000). During the 2-week study period, women took more steps than men (p=0.001), but the association between steps and RTL was only seen in men (p=0.05). Total steps taken (0.202, p=0.04) and sedentary time (-0.247, p=0.007) significantly correlated with RTLs in 70-year old subjects. Moderate PA changed RTL between the highest quartile and the three lower quartiles (0.023 between 4th and 1st, 0.04 between 4th and 2nd and 0.027 between 4th and 3rd) in the 70-year old subjects. Conclusions Women had longer RTL and performed higher exercise volume, via step count, compared to men. However, exercise volume and RTL correlated positively only in men. Surprisingly, age correlated negatively with RTL just within a maximum age of difference of 2 years. This suggests that telomere attrition rate accelerates in older age. Moderate physical activity at the time of the study was protective towards RTL.